Right ventricular and atrial strain in patients with advanced melanoma undergoing immune checkpoint inhibitor therapy. (27th July 2022) - Pohl, Julia; Totzeck, Matthias; Mincu, Raluca‐I.; Margraf, Simone M.; Scheipers, Lena; Michel, Lars; Mahabadi, Amir A.; Zimmer, Lisa; Rassaf, Tienush; Hendgen‐Cotta, Ulrike B.
Abstract: Aims: While immune checkpoint inhibitor (ICI) therapy significantly improves survival rates in advanced melanoma, ICI can evoke severe immune‐related cardiovascular adverse events. Right ventricular (RV) dysfunction negatively impacts the outcomes in cardiovascular diseases and may be an early sign for overall cardiotoxicity. We aimed to assess RV function in melanoma patients undergoing ICI therapy using conventional echocardiographic and strain imaging techniques. Methods and results: We retrospectively examined 30 patients (40% women, age 59 ± 13 years) with advanced melanoma (stage III/IV) before and 4 weeks after the start of ICI therapy (follow‐up at 39 ± 15 days); n = 15 of the patients received nivolumab, and n = 15 received the combination therapy nivolumab/ipilimumab. Two‐dimensional echocardiography with assessment of RV longitudinal strain of the free wall (RV‐LSFW) and assessment of right atrial (RA) strain from speckle tracking was performed at baseline and after the start of ICI therapy. Short‐term ICI therapy caused a reduction of RV‐LSFW (−25.5 ± 6.4% vs. −22.4 ± 4.3%, P = 0.002) and of RA strain during contraction phase (−10.6 ± 3.5% vs. −7.7 ± 3.1%, P = 0.001). Conventional parameters including tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), and pulmonary artery systolic pressure were not different between the two time points (TAPSE 26 ± 5 vs. 25 ± 5 mm, P = 0.125; FAC 38 ± 13% vs. 38 ± 14%, P = 0.750; and pulmonary artery systolic pressure 27 ± 10 vs. 25 ± 8 mmHg, P = 0.268). Conclusions: Analysis of RV and RA strain shows alterations even in a short‐term follow‐up, while changes in RV function are not visible by conventional RV parameters. Alterations in RV and RA strain could be early signs of cardiotoxicity and therefore should be assessed in patients undergoing ICI therapy.